Species Association of Corpse Storage Trees in Laiwangi Wanggameti National Park, East Nusa Tenggara - Ferdynan Dapadeda; Ervizal A. M. Zuhud; Agus Hikmat (Media Konservasi, 2017)
Indonesia has a high biodiversity with various uses. Sundacarpus amarus (Blume) C.N. Page. (Mbakuhau) and Tetrameles nudiflora R.Br. (Marra) located in the Laiwangi Wanggameti National Park East Sumba District, East Nusa Tenggara which are used by the community as corpse storage trees. Lack of information about the utilization of these plants causes the potential abandonment. This study aims to determine the species association of corpse storage trees with others and environmental factors that influence their spread. The method used is a combination between line and block at growth levels, that is seedling, sapling, pole and tree. The species association was analyzed by Chi Square Test and Jaccard Index Test. The results showed that S. amarus was associated with other species at various growth levels. Meanwhile, T. nudiflora was associated only at seedling and tree level. The presence and spread of S. amarus influenced by air humidity, light, elevation and soil temperature. T. nudiflora  plants are only exposed to temperature. Keywords: association, corpse storage trees, East Nusa Tenggara